Filipino maritime students and seafarers defying dominant social imaginaries - Mendoza, Valentin M. (Philippine Sociological Review, 2015)
This article explores the lives of Filipino maritime students and seafarers through the analysis of creative productions, such as photographs, artwork, video music and an accompanying ethnographic work. The study analyses 90 photographs consisting of 60 images sent as entries to a photography contest and 30 images retrieved from a Facebook page dedicated to seafarers. These images were used in photo elicitation interviews with seafarers and maritime students to capture their narratives.